Public participation and the politics of environmentalism - Jennifer Andrew; Ian Robottom (Environmental Association of Southern Africa, 1998)
Once, environmentalists called for new public virtues, now they call rather for better managerial strategies. Once, they advocated more democracy and local self reliance, now they tend to support the global empowerment of governments, corporations and science. Once, they strove for cultural diversity, now they see little choice but to push for a worldwide rationalisation of life-styles. Indeed, as ecological issues have moved to the top of the agenda of international politics, environmentalism appears in many cases to have lost the spirit of contention, limiting itself to the provision of survival strategies for the powers that be. As a result, in recent years a discourse of global ecology has developed that is largely devoid of any consideration of power relations, cultural authenticity and moral choice; instead, it rather promotes the aspirations of a rising eco-cracy to manage nature and regulate people worldwide. Ironically, a movement which once invited people to humility has produced experts who succumb to the temptation of hubris (Sachs, 1993:xv)